Maximum Power Point Tracking of Wind Turbine Conversion Chain Variable Speed Based on DFIG - H. Becheri; I. K. Bousarhanne; A. Harrouz; H. Glaoui; T. Belbekri (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
Wind energy has many advantages, it does not pollute and it is an inexhaustible source. However, the cost of this energy is still too high to compete with traditional fossil sources. The yield of a wind turbine depends on three parameters: the power of the wind, the turbine power curve and the ability of the generator to respond to fluctuations in the wind. This article presented the MPPT of a wind turbine system equipped with an asynchronous generator has dual power under MatlabSimulink program, in the first time we simulated all the conversion chain with complete model of DFIG and vector control in second stepthen applied the extracted maximum power MPPT strategists, this command is effective and has several advantages it offered to kept the maximum power delivered to network despite all the parameter is change.